Alpha thalassaemia due to non-deletional mutations on the -3.7 alpha globin fusion gene: Laboratory diagnosis and clinical importance - Chow, A.; Ghassemifar, Reza; Finlayson, J. (2013)
Aims: Alpha (α) thalassaemia may be caused by large deletions of the α globin gene(s), or rarely, non-deletional mutations. Both types of mutations may co-exist, and if located on the same allele (α0), produce a reproductive risk of hydrops fetalis. We illustrate how clinical-laboratory correlation and accurate α gene sequencing are essential in identifying such patients. Method: Nine asymptomatic patients with - α 3.7 thalassaemia trait were noted to have significant microcytosis that was insufficiently explained by a single α deletion. Hence α1 and α2 globin gene sequencing were performed, which detected a non-deletional mutation in all patients. A new set of α1 specific primers were designed for separate sequencing of the α1 gene and the - α 3.7 fusion gene, respectively, so that the non-deletional mutation could be localised to the correct allele. Results: In six of nine patients tested, the non-deletional mutation was on the α1 globin gene. In three patients the mutation was located on the - α 3.7 fusion gene. The latter group functionally has an α0 allele (αα/–) with a reproductive risk for Hb Barts hydrops fetalis. Conclusion: Non-deletional mutations can occur on the α globin gene or a fusion gene such as the - α3.7 allele. Identification and accurate localisation of these mutations is important as this can have significant reproductive implications.